264 Cognitive and imaging correlates in cerebral amyloid angiopathy subthypes. Issue 6 (27th May 2022) - Bonifacio, Guendalina; Chan, Edgar; Islam, Afm; Werring, David
Abstract : Common clinical subtypes of CAA are CAA with intracerebral haemorrhage (CAA-ICH), with cognitive decline (CAA-cog), and with Transient Focal Neurological Episodes (CAA-TFNE); most studies of cognition and neuroimaging to date have focussed on CAA-ICH. We therefore evaluated the cognitive and imaging phenotypes across all the CAA subgroups. This is a retrospective cross-sectional study of cognition and imaging in 99 patients; 70 (71%) with CAA and 29 (29%) with presumed hypertensive arteriopathy (non-CAA). We measured impairment across the cognitive domains using a standardised test battery, and we described the imaging biomarkers via visual rating of standardised MRI scans. Most patients had impairment in more than 2 domains (69%). We found impairment in the executive domain in 71% of patients, followed by non-verbal IQ (59%) and verbal IQ (48%). Patients with CAA-TFNE had similar impairments across cognitive domains to CAA-ICH. CAA-cog performed worse than CAA-ICH with verbal recognition memory (p<0.05). With regards to imaging findings, the groups differed significantly for several small vessel disease markers (e.g. moderate to severe cSS in CAA-TFNE compared to CAA-ICH and CAA-cog, >2 lobar CMBs in CAA-ICH and CAA-cog compared to CAA-TFNE). Our findings confirm high rates of cognitive impairment across CAA subtypes, including CAA-TFNE. The cognitive profile of CAA-TFNE was similar to that of CAA-ICH, despite differences in neuroimaging findings. Hence, the effects of CAA on cognition can occur regardless of the presence of ICH. guendabonifacio@gmail.com